Cationic Comb-Type Copolymer Excludes Intercalating Dye from DNA Without Inducing DNA Condensation - Maruyama, Atsushi; Sonda, Naotaka; Yamasaki, Kohei; Hirano, Masanori; Kidoaki, Satoru; Shimada, Naohiko; Maeshiro, Masatoshi; Miyazaki, Masaya (Current Nanoscience, 2014)
The interaction of a single molecule of DNA with cationic comb-type copolymers has been observed using a flow-stretch assay. We have shown that interaction with a copolymer with a high degree of grafting did not cause a coil-to-globule transition but resulted in shrinkage of the DNA by 20%. In this study, a flow-stretch assay was employed in which changes in length and fluorescence intensity of DNA were simultaneously observed. Upon binding of fluorescent intercalator dyes, the DNA length was extended. In the presence of copolymer, dye binding was inhibited and DNA length was not significantly different than that in the absence of dye and copolymer. Our data suggest that the copolymer does not influence DNA length. Our observation implies that use of the fluorescence dye exclusion assay to estimate DNA condensing activity of polycations must be carefully carried out.
Keywords: Compaction